2016
DOI: 10.3982/te1905
|View full text |Cite
|
Sign up to set email alerts
|

Large deviations and stochastic stability in the small noise double limit

Abstract: We consider a model of stochastic evolution under general noisy best-response protocols, allowing the probabilities of suboptimal choices to depend on their payoff consequences. Our analysis focuses on behavior in the small noise double limit: we first take the noise level in agents' decisions to zero, and then take the population size to infinity. We show that in this double limit, escape from and transitions between equilibria can be described in terms of solutions to continuous optimal control problems. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 38 publications
0
38
0
Order By: Relevance
“…Our framework also differs fromSandholm and Staudigl (2015), who studied the rate at which certain types of stochastic learning dynamics converge to the stochastically stable equilibrium. In games with multiple equilibria, the convergence time can also grow exponentially with N.8 In a similar spirit,Pradelski (2015) showed that by introducing aggregate shocks to a twosided matching market, the convergence time becomes polynomial in the number of players, rather than exponential.…”
mentioning
confidence: 99%
“…Our framework also differs fromSandholm and Staudigl (2015), who studied the rate at which certain types of stochastic learning dynamics converge to the stochastically stable equilibrium. In games with multiple equilibria, the convergence time can also grow exponentially with N.8 In a similar spirit,Pradelski (2015) showed that by introducing aggregate shocks to a twosided matching market, the convergence time becomes polynomial in the number of players, rather than exponential.…”
mentioning
confidence: 99%
“…There are strong reasons to expect this double limit to be analytically tractable. In Sandholm and Staudigl (2016), we study the reverse order of limits, under which the noise level η is first taken to zero, and then the population size N to infinity. For this order of limits, we show that large deviations properties are determined by the solutions to piecewise linear control problems, and that these problems can be solved analytically.…”
Section: Discussionmentioning
confidence: 99%
“…Since the logit protocol is parameterized by a noise level and since clever payoff evaluation is used, this example satisfies the assumptions of our analysis of the small noise double limit inSandholm and Staudigl (2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To find the cost of least cost transitions between conventions, Sandholm and Staudigl [304], building on Staudigl [337], show that, as a finite population grows large, transition costs can be approximated by solutions to continuous optimal control problems. They illustrate the method by analyzing stochastic stability under logit choice of three strategy coordination games that satisfy the marginal bandwagon property of (Kandori and Rob [190]), under which, for strategies i, j, k, i / ∈ {j, k},…”
Section: Least Cost Transition Pathsmentioning
confidence: 99%